A public relations event management project for the Nanyang Technological University Students' Union. - Lee, Hwee Chin. (2009)
This project aims to examine the role and extent of public relations in educational institutions, focusing on a non-profit student organisation, by drawing comparisons and contrasts with earlier research on public relations and its relationship with non-profit organisations. Modem public relations can contribute significantly to the organisation, of both non-profit and business nature, so long as it is operated from the management’s support and understanding of its role in the organisation. As the industry faces more challenges ahead, there is a vital need for public relations to find a creative niche, in planning programmes and directing organisational goals, to benefit both the orgmisation and its publics. The proposed project, to be guided by these various objectives in mind, would offer and test thc local and practical perspective of the cxtent public relations is employed in a non-profit organisation through a special one-off event. We believe that public relations, as an industry, has much potential to grow and fulfil its social responsibility function as more people are aware of the importance and power of communication. By harnessing public relations, non-profit organisations would be more adept and equipped at communicating with their key publics, advancing towards a tmly harmonious and rewarding relationship.